(3GdGfJUGQ Ydi YdeGA GdCeUGQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3jHOC CKfGA GdELGRI hChd GdehLhO efg (B: (3GdMce GdChd VeGf bjeI GdMed , hgPG gh QCi CFeI GdYJQI , heMci Yf GdaQjbjf GdMfajI hGdTGaYjI s
(3BNQgG (B:s
(3jfJgi HHGH GdQgf , hBNQg bhdg (B:" (3hEf cGf GdOjf eTQhWkG dCf GdTQW Cedc hHJeGeg jJe GdcdGe ai GdaUd GdKGdK eeG jJYdb HGdbHV ai Mb GdQGgf hGdeQJgf s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3abg GdgOhjI (B309) s
Keywords: (3abg GdePGgH GdCNQis